Effect of a novel dietary supplement Khejri, and Spirulina supplementation on lipid profile in cricket players - Pareek, Arvind; Kasvan, Bhanwra Ram; Singh, Neha (Frontiers in Sports and Active Living, 2023)
Prosopis cineraria (Fabaceae) is known as Khejri in India or the golden tree of Indian deserts. It’s potential as a dietary supplement in sports nutrition and its effect on regulating lipid profile has never been investigated. Spirulina is a superfood with high nutritional value and is a popular supplement among athletes. In the current study, Spirulina and Khejri were used as supplements by cricket players to improve their physical fitness and lipid profile. Both supplements were given to individual groups and in combination to see the combined effect. The intervention period was 21 days, and supplements were given in 500 mg doses daily. Lipid profile assessments were done before and after the intervention period. 40 cricket players were divided into 4 groups: Group 1 (n=10): Both supplements, Spirulina and Khejri, Group 2 (n=10): Supplement Spirulina, Group 3 (n=10): Supplement Khejri, and Group 4 (n=10): Control. When experimental groups 1, 2 and 3 were compared to the control group 4, significant reduction was observed in triglyceride levels (Group1 vs control: 141.53±14.74 vs 199.28±27.24, p<0.05; Group 2 vs control: 137.5±14 vs 199.28±27.24, p<0.05; Group 3 vs control: 135.32± 17.34 vs 199.28±27.24, p<0.05) and significant reduction in cholesterol levels was found post-intervention after 21 days of supplementation (Group1 vs control: 149.75±7.08 vs 207.86±11.69, p<0.001; Group 2 vs control: 178.28±9.43 vs 207.86±11.69, p<0.05; Group 3 vs control: 142.92± 10.01 vs 207.86±11.69, p<0.001). Cholesterol and Triglyceride levels were significantly decreased pre- vs. post-intervention by Khejri and Spirulina supplements in cricket players.